Effects of Crude Protein and Amino Acid to Lysine Ratio on Finishing Pig Growth Performance and Carcass Characteristics - M. A. Gonçalves; M. D. Tokach; S. S. Dritz; K. Touchette; J. M. DeRouchey; J. C. Woodworth; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2016)
The increased availability of synthetic amino acids has reduced the amount of intact protein sources used in swine diets. The objective of this study was to determine the effects of different CP levels and AA to Lys ratios on growth performance and carcass characteristics in late finishing pigs. A total of 1,682 pigs (327 × 1050, PIC, Hendersonville, TN; initially 252.7 lb BW) were used in a 25-d growth trial arranged in an unbalanced randomized complete block design with 25 pigs per pen and initially 8 or 16 pens per treatment. Dietary treatments were arranged in a 2 × 2 + 1 factorial consisting of combinations of 10.3 or 13.5% CP and 2 AA to Lys ratios plus a control diet (13.5% CP from soybean meal). The standardized ileal digestible (SID) ratios to Lys were 55% Met+Cys, 68% Thr, 17% Trp, 65% Val, 56% Ile, and 32% His for PIC (2013) and 60% Met+Cys, 68% Thr, 20% Trp, 72% Val, 55% Ile, and 37% His for the Modified ratio. Overall, from d 0 to 25, pigs fed the control diet had increased ADG (P<0.001) compared with pigs fed diets formulated with the PIC or Modified AA:Lys ratios. There were no statistical differences in ADFI observed between the treatments. For F/G, there was a 2-way marginally significant interaction (P = 0.066) where F/G was improved for pigs fed the PIC AA:Lys ratios with 13.5% CP compared to those fed diets with 10.3% CP; however, there were no statistical differences in F/G between CP levels in pigs fed Modified AA:Lys ratios. Final BW was increased in pigs fed the control compared to pigs fed diets formulated with the PIC (P = 0.017) or Modified (P<0.001) AA:Lys ratios. Pigs fed 10.5% CP provided by glutamic acid and glycine, regardless of AA:Lys ratio, had increased (P = 0.031) carcass yield; however, there was no statistical differences between the dietary treatments regarding HCW, backfat, loin depth, and percentage lean. In conclusion, reducing intact protein (soybean meal) decreased growth performance and the inclusion of a nitrogen source (glycine and glutamic acid) was not able to recover growth performance in this commercial study. The 2 amino acid ratios in the low crude protein diets evaluated in this study did not improve growth performance or carcass characteristics.
Keywords: amino acid ratio; crude protein level; growth; finishing pig